The role of osterix in osteoblastic differentiation: Potential in the treatment of osteoarticular affections (Veterinary Science, 2019)
This paper revises the Osterix protein and its role in the skeletongenesis, the endochondral ossification and in various pathological processes of the osteoarticular systems in animals. Osterix is a transcription factor of the family of bone morphogenic proteins, which promptsbone formation. In the skeletogenesis Osterix allows the differentiation of the preosteoblasts into osteoblasts and the maturity and differentiation of osteoblasts into osteocytes. In the endochondral ossification, Osterix expresses in the mature and hypermature chondrocytes and contributes to degrade the cartilage matrix. In the extrauterinelife, it collaborates in the regulation of the bone homeostasis and it is involved in osteoarticular pathologies, in bone oncology and in the repair of fractures. Learning about the action of Osterix on the bone cells and chondrocytes is an attractive starting point for further research aiming at contributing to the diagnosis and treatment of diseases of the osteoarticular system in animals.
Keywords: Osterix; Preosteoblast; osteoblast; cell differentiation; bone.